Application of software requirement engineering for ontology construction - Supavas Sitthithanasakul (2018)
© 2017 IEEE. One of the most accepted tool for represent information in knowledge management application is the ontology. There are many theory describe for ontology development method but in a loosely instruction. This paper contributes the new method to develop ontology by using a structured model of the software requirement engineering process. We demonstrate that requirement engineering process can provide a guideline such that ontology to be built systematically.